2016
DOI: 10.1080/15592324.2016.1224045
|View full text |Cite
|
Sign up to set email alerts
|

Kin recognition is a nutrient-dependent inducible phenomenon

Abstract: Recognition and response to prospective competitors are crucial variables that must be considered in resource distribution and utilization in plant communities. Associated behaviors are largely mediated through the exchange of low-molecular weight exudates. These cues can significantly alter the root system architecture (RSA) between neighboring plants and are routinely sensitive enough to distinguish between plants of the same or different accessions, a phenomenon known as kin recognition (KR). Such refined d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 35 publications
(57 reference statements)
1
26
0
Order By: Relevance
“…The impact of root competition on root placement patterns and behavioral responses is well known (Bartelheimer et al ., ; Semchenko et al ., ; Schmid et al ., ). Recent studies have shown that root exudates may alter root architecture during kin recognition in plants (Semchenko et al ., ; Palmer et al ., ). This study indicated that the focal rice cultivars could optimize their root systems in response to kin or nonkin.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The impact of root competition on root placement patterns and behavioral responses is well known (Bartelheimer et al ., ; Semchenko et al ., ; Schmid et al ., ). Recent studies have shown that root exudates may alter root architecture during kin recognition in plants (Semchenko et al ., ; Palmer et al ., ). This study indicated that the focal rice cultivars could optimize their root systems in response to kin or nonkin.…”
Section: Discussionmentioning
confidence: 97%
“…These signals trigger complex plant response strategies, such as shade avoidance, alteration of biomass allocation patterns, and biochemical behaviors (Bais, ; Crepy & Casal, ). Although chemical‐mediated kin recognition responses may take place through aboveground volatiles, most evidence suggests root exudates as the signal of relatedness (Biedrzycki et al ., , ; Semchenko et al ., ; Palmer et al ., ). In this study, kin recognition responses still occurred with nylon mesh that segregated root systems, indicating that kin recognition in rice lines is driven by root‐secreted chemicals or microbial interactions rather than direct root contact.…”
Section: Discussionmentioning
confidence: 97%
“…The collection of root exudates, in the forms of solutions (Biedrzycki et al., 2010) or leachates (Semchenko et al., 2014), from themselves and neighbours may differ from each other not only in the identity cues but also in nutrient composition. Thus, the nutrient contents, nitrogen and phosphorus in particular (Palmer et al., 2016), in the collections should be adjusted to a similar level before exposing focal plants to these collections.…”
Section: Further Thoughts On the Experimental Designs For Testing Thementioning
confidence: 99%
“…Beyond their role in regulating plant-microbial associations, insights into the plant’s contribution to this signaling landscape has emerged from studies on: (i) host recognition by parasitic plants [ 9 12 ], (ii) kin recognition/selection [ 13 16 ], and (iii) allelopathy [ 17 , 18 ]. Our understanding of the redox dynamics of these chemical networks has expanded significantly with the discovery of semagenesis [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%